Historical approach toward America's presence stabilization strategy in the Persian Gulf - Heidari, Hossein; Jalalpoor, Shiva (Journal of History Culture and Art Research, 2017)
Persian Gulf links three continents of Europe, Asia and Africa together and was the center of attention in the past by hegemonic powers to access India from the shortest way but nowadays, Persian Gulf's strategic situation is undeniable. England and the US are among the countries of which presence in Persian Gulf has been more than other powers. After England's claim of soldiers' withdrawal from the region in 1968 until 1971 and ending their military presence in this region and east of Suez, the US tried to fill the gap. The findings of this study revealed that in recent years, military strategy of the US has been higher than others. Plans of US for dominating Persian Gulf, has been based on specific goals, regional special conditions and supporting their allies. This study aims to investigate the reasons of the US presence and its strategies in Persian Gulf region.